Osteoblast mineralization requires β1 integrin/ICAP-1-dependent fibronectin deposition - Brunner, Molly; Millon-Frémillon, Angélique; Chevalier, Genevieve; Nakchbandi, Inaam; Mosher, Deane; Block, Marc R.; Albigès-Rizo, Corinne; Bouvard, Daniel (The journal of cell biology, 2011)
The morphogenetic and differentiation events required for bone formation are orchestrated by diffusible and insoluble factors that are localized within the extracellular matrix. In mice, the deletion of ICAP-1, a modulator of β1 integrin activation, leads to severe defects in osteoblast proliferation, differentiation, and mineralization and to a delay in bone formation. Deposition of fibronectin and maturation of fibrillar adhesions, adhesive structures that accompany fibronectin deposition, are impaired upon ICAP-1 loss, as are type I collagen deposition and mineralization. Expression of β1 integrin with a mutated binding site for ICAP-1 recapitulates the ICAP-1-null phenotype. Follow-up experiments demonstrated that ICAP-1 negatively regulates kindlin-2 recruitment onto the β1 integrin cytoplasmic domain, whereas an excess of kindlin-2 binding has a deleterious effect on fibrillar adhesion formation. These results suggest that ICAP-1 works in concert with kindlin-2 to control the dynamics of β1 integrin-containing fibrillar adhesions and, thereby, regulates fibronectin deposition and osteoblast mineralization.
Gesehen am 28.06.2021